A laminar box apparatus for 1g testing of granular columns embedded in soft clay. Issue 1 (22nd February 2019) - Cengiz, Cihan; Guler, Erol
Abstract : Ordinary stone columns and geosynthetic-encased columns are widely used as a method of soil improvement for soft clay deposits. The behaviour of encased and unencased columns under the action of dynamic loads are not thoroughly understood. In order to shed light into the dynamic behaviour of granular columns and column-enhanced soft soil deposits, a novel large-scale laminar box assembly is designed together with provisions for instrumentation, consolidation of clay slurry and casing pipe pushing units for column installation. The laminar box is comprised of 16 individually supported laminates. The laminar box has inner areal footprint dimensions of 900 × 900 mm and a height of 1932 mm. The laminar box is utilised to study the behaviour of granular columns of varying reinforcement stiffnesses under dynamic loads. In order to make a thorough comparison of reinforcement stiffnesses on column behaviour, columns with different reinforcement arrangements are installed together in the same clay bed, and scaled earthquake accelerograms and sinusoidal base excitations are applied. Column response is studied through the reinforcement strains occurring on the encasement and the amount of vertical pressure sustained on the column during the dynamic load cases.